Configuration‐based approach for topological problems in the design of wireless sensor networks. (16th November 2018) - Morais, Vinicius; Mateus, Geraldo Robson
Abstract: In this paper, we deal with two routing problems that integrate coverage and cardinality constraints to optimize the wireless sensor networks lifetime. Problems based on arborescence and cycle topologies are defined on the design of that kind of network. We propose configuration‐based linear integer programming formulations and devise column‐and‐row generation (CRG) algorithms to evaluate the bounds. Computational experiments showed that configuration‐based formulations dominate the formulations being compared and indicate CRG as an alternative to solve related location–allocation problems in transportation and telecommunication networks.